2016
DOI: 10.1080/21691401.2016.1192040
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol loaded lecithin/chitosan nanoparticles: preparation, characterization, and their potential applications as a sustainable antifungal agent

Abstract: Flavonoid compounds are strong antioxidant and antifungal agents but their applications are limited due to their poor dissolution and bioavailability. The use of nanotechnology in agriculture has received increasing attention, with the development of new formulations containing active compounds. In this study, kaempferol (KAE) was loaded into lecithin/chitosan nanoparticles (LC NPs) to determine antifungal activity compared to pure KAE against the phytopathogenic fungus Fusarium oxysporium to resolve the bioav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 28 publications
5
57
1
Order By: Relevance
“…The spectroscopy results indicated that the intramolecular hydrogen bonding was structured between PE and AgNPs after the formation of P-AgNPs [18]. Surface properties of nanomaterials have an important effect on drug release kinetics [26]. Interestingly, when the results of the size and surface morphology of P-AgNPs compared with the results data of TEM micrograph, the size of P-AgNPs within increased amount of PE decreased from 150.90-47.72 nm, but the size of AgNPs increased from 14.16-16.42 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The spectroscopy results indicated that the intramolecular hydrogen bonding was structured between PE and AgNPs after the formation of P-AgNPs [18]. Surface properties of nanomaterials have an important effect on drug release kinetics [26]. Interestingly, when the results of the size and surface morphology of P-AgNPs compared with the results data of TEM micrograph, the size of P-AgNPs within increased amount of PE decreased from 150.90-47.72 nm, but the size of AgNPs increased from 14.16-16.42 nm.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in inhibition was observed at 7 days post-treatment, compared to active alone [81]. In another trial, kaempferol (another low-soluble fungicide) loaded onto lecithin/chitosan showed 67% inhibition efficacy after 60 days storage on a Fusarium oxysporum-infected Petri dish [85].…”
Section: Nanoparticles As Carriers For Fungicidesmentioning
confidence: 99%
“…The use of SACPNs for the encapsulation and delivery of antibacterial agents has received increasing attentions. For instance, kaempferol (KAE) is loaded into SACPNs and compared with pure KAE to determine antifungal activity against the phytopathogenic fungus, as illustrated schematically and shown by the microscopic images in Figure 12(a and b) (Ilk et al, 2017). KAE can be successfully encapsulated in SACPNs with an efficiency of 93.8 ± 4.28% and the generated SACPNs show good physicochemical stability.…”
Section: Antibacterialmentioning
confidence: 99%